Social Support and Self-Efficacy of Adolescents for the Prevention of Drug Use in Indonesia - Sri Jumiati; Teuku Tahlil; Marthoenis Marthoenis (Malahayati Nursing Journal, 2025)
ABSTRACTDrug abuse remains a significant public health issue in Indonesia, particularly among adolescents. Individuals aged 15–18 years are at heightened risk due to social pressure, inadequate information, and low levels of social support and self-efficacy. This study aimed to examine the relationship between social support and adolescent self-efficacy in the prevention of drug use. A correlational research design was employed, involving 80 adolescents aged 15–18 years. Data were analyzed to determine the association between social support and self-efficacy in drug use prevention. The findings revealed a significant positive relationship between social support and self-efficacy (p=0.018). It can be concluded social support and self-efficacy are significantly associated with the prevention of drug use among adolescents. Interventions to strengthen these factors may contribute to reducing drug abuse in this vulnerable population. Keywords: Adolescent Drug Prevention, Social Support, Self-Efficacy, Public Health, Indonesia, Drug Abuse Prevention.